Amine-Catalyzed Cascade Reactions of Unprotected and Unactivated Carbohydrates: Direct Access to C-Glycosides - Witte, Swjatoslaw N. R.; Voigt, Benjamin; Mahrwald, Rainer (Synthesis, 2015)
Unprotected carbohydrates were reacted in amine-catalyzed cascade reactions with various methyl ketones to give a direct access to C-glycosides by an operationally simple protocol. As the reaction mechanism, an aldol condensation followed by an intramolecular conjugate addition is assumed.
Keywords: C-glycosides; unprotected carbohydrates; amine catalysis; cascade reaction; intramolecular conjugate addition